Method for producing article, adhesive composition, and foamable adhesive sheet

By using thermally expandable microcapsules as foaming agent in the bonding process and adjusting the heating conditions to make the heating conditions of the foaming agent and the adhesive composition meet a specific slope relationship, the problem of reducing bonding strength is solved, and the heating conditions of the foaming agent and adhesive composition are realized. High reliability and durability of components.

CN119487147APending Publication Date: 2025-02-18DAI NIPPON PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380046818.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the adhesive composition containing the foaming agent, the bonding strength is easily reduced, resulting in a decrease in reliability and durability of the member.

Method used

By using thermally expandable microcapsules as foaming agent in the bonding process and performing differential scanning calorimetry measurement under heating conditions, the heating conditions of the foaming agent and the adhesive composition are adjusted to foam the foaming agent. The rate-time curve and the DSC curve of the adhesive composition satisfy a specific slope relationship (A

Benefits of technology

By adjusting the heating conditions, the thermosetting resin can be sufficiently cured before the foaming agent shrinks, thereby improving the bonding strength and enhancing the reliability and durability of the member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487147A_ABST
    Figure CN119487147A_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for manufacturing an article, the method comprising: a disposing step of disposing an adhesive composition containing a thermosetting resin and a foaming agent between a first member and a second member; and a bonding step for bonding the first member and the second member by heating the adhesive composition and foaming and curing the adhesive composition, the foaming agent being a thermally expandable microcapsule. When differential scanning calorimetry is performed on the foaming agent using a camera-mounted differential scanning calorimeter under heating conditions in the bonding step, the foaming rate-time curve takes time as the horizontal axis and takes the foaming rate of the foaming agent as the vertical axis. When the adhesive composition is subjected to differential scanning calorimetry under heating conditions in the bonding step, the slope of a tangent line drawn from the apex of a peak in a curve on the long-time side of the peak is A, and when the adhesive composition is subjected to differential scanning calorimetry under the heating conditions in the bonding step, A represents the slope of a tangent line drawn from the apex of the peak. A is less than B, where A is the slope of a tangent leading out from the apex of the exothermic peak in a curve on the long-term side of the exothermic peak, and B is the slope of a tangent leading out from the apex of the exothermic peak in a foaming rate-time curve using time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when differential scanning calorimetry is performed on the foaming agent using a camera-mounted differential scanning calorimeter. When the time at the peak of the peak is defined as T1 and the time at the peak of the exothermic peak is defined as T2 in a DSC curve with the time as the horizontal axis and the heat flow as the vertical axis when the composition obtained by removing the foaming agent from the adhesive composition is subjected to differential scanning calorimetry, the time at the peak of the exothermic peak is set as T1 in the bonding step, and the time at the peak of the exothermic peak is set as T2 in the DSC curve with the time as the horizontal axis and the heat flow as the vertical axis. The adhesive composition is heated such that T1 < T2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing an article, and an adhesive composition and a foamable adhesive sheet used therein. Background Art

[0002] Adhesives for bonding components to each other are used in a variety of fields, and various bonding methods are known.

[0003] In recent years, it has been proposed to use an adhesive composition containing a foaming agent (for example, Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6223477

[0007] Patent Document 2: Japanese Patent Application Publication No. 2019-203062 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Regarding heating conditions in an adhesive composition containing a foaming agent, for example, Patent Document 1 discloses that when the thermal foaming temperature (foaming start temperature) of the thermal foaming agent is set to T1 and the curing start temperature of the adhesive layer is set to T2, the relationship T1≤T2 is satisfied.

[0010] However, the inventors of the present disclosure have studied the heating conditions of the adhesive composition containing a foaming agent, and found that even when the foaming start temperature of the foaming agent and the curing start temperature of the adhesive layer are set to a given relationship, the bonding strength may decrease. If the bonding strength decreases, there will be problems such as poor reliability and durability of components bonded by the adhesive composition containing a foaming agent.

[0011] The present disclosure has been made in view of the above-mentioned actual situation, and its main object is to provide a method for producing an article capable of improving adhesive strength, and an adhesive composition and a foamable adhesive sheet used therein.

[0012] Means for solving problems

[0013] One embodiment of the present disclosure provides a method for manufacturing an article, the manufacturing method comprising: a placement step of placing an adhesive composition containing a thermosetting resin and a foaming agent between a first member and a second member; and a bonding step of heating the adhesive composition to foam and solidify it, and bonding the first member to the second member, the foaming agent being a thermally expandable microcapsule, and in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when differential scanning calorimetry is performed on the foaming agent using a differential scanning calorimeter equipped with a camera under the heating conditions in the bonding step, a slope of a tangent drawn at the top of a peak in the curve on the long time side of the peak is set to A, and the adhesive composition is subjected to the heating conditions in the bonding step. In a DSC curve with time as the horizontal axis and heat flow as the vertical axis when differential scanning calorimetry is performed on the foaming agent using a differential scanning calorimeter equipped with a camera, the slope of a tangent drawn at the apex of the exothermic peak in the curve on the long time side of the exothermic peak is set to B. In this case, A<B. In a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when differential scanning calorimetry is performed on the foaming agent using a differential scanning calorimeter equipped with a camera, the time of the apex of the peak is set to T1. In a DSC curve with time as the horizontal axis and heat flow as the vertical axis when differential scanning calorimetry is performed on a composition obtained by removing the foaming agent from the adhesive composition, the time of the apex of the exothermic peak is set to T2. In this case, in the bonding step, the adhesive composition is heated in such a manner that T1<T2.

[0014] Another embodiment of the present disclosure provides an adhesive composition, comprising a thermosetting resin and a foaming agent, wherein the foaming agent is a heat-expandable microcapsule, and in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry using a differential scanning calorimeter equipped with a camera under heating conditions in which the temperature is raised from room temperature to the maximum foaming temperature of the foaming agent in 5 minutes and the temperature is maintained at the maximum foaming temperature of the foaming agent, a slope of a tangent drawn at the apex of the peak in the curve on the long-time side of the peak is set to C, and in a DSC curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under the above heating conditions, a slope of a tangent drawn at the apex of the exothermic peak in the curve on the long-time side of the exothermic peak is set to D, and in this case, C<D.

[0015] Moreover, another embodiment of the present disclosure provides a foamable adhesive sheet having an adhesive layer, wherein the adhesive layer contains the above-mentioned adhesive composition.

[0016] Effects of the Invention

[0017] The method for producing an article disclosed herein has the effect of improving the bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a process diagram illustrating a method for manufacturing the article of the present disclosure.

[0019] Figure 2 This is a schematic cross-sectional view illustrating the foamable adhesive sheet of the present disclosure.

[0020] Figure 3 This is a graph illustrating a foaming rate-time curve of a foaming agent.

[0021] Figure 4 This is a graph illustrating a DSC curve of an adhesive composition.

[0022] Figure 5 This is a graph illustrating a foaming rate-time curve of a foaming agent and a DSC curve of an adhesive composition.

[0023] Figure 6 The graphs illustrate a foaming rate-time curve of a foaming agent and a DSC curve of a composition obtained by removing the foaming agent from the adhesive composition.

[0024] Figure 7 This is a schematic cross-sectional view illustrating the foamable adhesive sheet of the present disclosure.

[0025] Figure 8 This is a schematic cross-sectional view illustrating the foamable adhesive sheet of the present disclosure.

[0026] Fig. 9 This is a graph showing, for the adhesive compositions of Production Examples 1 to 3, a foaming rate-time curve regarding a foaming agent and a DSC curve regarding the adhesive composition.

[0027] Fig.10 This is a graph showing, for example, a foaming rate-time curve of the adhesive composition 1 with respect to the foaming agent and a DSC curve of a composition in which the foaming agent is removed from the adhesive composition.

[0028] Fig.11 This is a graph showing, for Adhesive Composition 4, a foaming rate-time curve regarding a foaming agent and a DSC curve regarding a composition in which the foaming agent is removed from the Adhesive Composition.

[0029] Fig.12 This is a graph showing the relationship between the heating temperature, the holding time at the heating temperature, and the adhesive strength.

[0030] Fig.13 This is a graph showing the relationship between the heating temperature, the holding time at the heating temperature, and the cohesive failure rate. DETAILED DESCRIPTION

[0031] The following describes the embodiments of the present disclosure with reference to the accompanying drawings, etc. However, the present disclosure can be implemented in a variety of different ways and should not be construed as being limited to the contents of the embodiments illustrated below. In addition, in order to make the description clearer, the drawings sometimes schematically represent the width, thickness, shape, etc. of each part compared to the actual method, but it is only an example after all and does not limit the interpretation of the present disclosure. In addition, in this specification and each figure, the same symbols are sometimes used for the same elements as those described previously with respect to the figures that have already appeared, and the detailed description is appropriately omitted.

[0032] In this specification, when expressing the manner of arranging other components on a certain component, if it is simply expressed as "on..." or "under...", unless otherwise specified, it includes two cases: the case where the other components are arranged directly above or directly below the certain component in a manner of contacting with the certain component, and the case where the other components are arranged above or below the certain component with another component further interposed therebetween. In addition, in this specification, when expressing the manner of arranging other components on the surface of a certain component, if it is simply expressed as "on the side of..." or "on the surface of...", unless otherwise specified, it includes two cases: the case where the other components are arranged directly above or directly below the certain component in a manner of contacting with the certain component, and the case where the other components are arranged above or below the certain component with another component further interposed therebetween.

[0033] In this specification, a “sheet” also includes a member called a “film.” In addition, a “film” also includes a member called a “sheet.” In addition, the numerical range in this specification is a range of average values.

[0034] Hereinafter, the method for producing the article of the present disclosure, and the adhesive composition and foamable adhesive sheet used therein will be described in detail.

[0035] A. How the item is made

[0036] The manufacturing method of the article disclosed in the present invention comprises: a placement step of placing an adhesive composition containing a thermosetting resin and a foaming agent between a first member and a second member; and a bonding step of heating the adhesive composition to foam and solidify it, and bonding the first member and the second member, wherein the foaming agent is a thermally expandable microcapsule, and when the foaming agent is subjected to differential scanning calorimetry under the heating conditions in the bonding step using a differential scanning calorimeter equipped with a camera, in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis, the slope of a tangent drawn at the top of the peak in the curve on the long time side of the peak is set to A, and when the adhesive composition is subjected to differential scanning calorimetry under the heating conditions in the bonding step, the slope of a tangent drawn at the top of the peak is set to A. In the DSC curve with time as the horizontal axis and heat flow as the vertical axis during the measurement, the slope of the tangent drawn at the apex of the exothermic peak in the curve on the long time side of the exothermic peak is set to B. In this case, A<B. In the foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the above-mentioned foaming agent is measured by differential scanning calorimetry using a differential scanning calorimeter equipped with a camera, the time of the apex of the peak is set to T1. In the DSC curve with time as the horizontal axis and heat flow as the vertical axis when the above-mentioned adhesive composition is subjected to differential scanning calorimetry, the time of the apex of the exothermic peak is set to T2. In this case, in the above-mentioned bonding step, the above-mentioned adhesive composition is heated so that T1<T2.

[0037] The method for producing the article of the present disclosure will be described with reference to the drawings. Figure 1 (a) to (b) are process diagrams illustrating a method for manufacturing the article of the present disclosure. Figure 1 (a) to (b) are used Figure 2 An example of a method for manufacturing an article of a foamable adhesive sheet as exemplified in Figure 2 As shown in FIG. 1 , the foamable adhesive sheet 10 has an adhesive layer 1 containing an adhesive composition, wherein the adhesive composition contains a thermosetting resin and a foaming agent. In the method for manufacturing an article, first, as Figure 1 As shown in (a), a foamable adhesive sheet 10 is disposed between the first member 20a and the second member 20b. Figure 1 As shown in (b), the adhesive composition contained in the adhesive layer of the foamable adhesive sheet 10 is heated to foam and solidify. The first member 20a and the second member 20b are bonded (joined) by the foamed and solidified adhesive sheet 11. Thus, the article 100 having the adhesive sheet 11 disposed between the first member 20a and the second member 20b is obtained.

[0038] In the present disclosure, the foaming agent is a heat-expandable microcapsule, and a heat-expandable agent such as hydrocarbon is contained inside a shell containing a resin. Here, in the heat-expandable microcapsule, if heating is applied, the resin constituting the shell softens, and at the same time, the pressure of the heat-expandable agent such as hydrocarbon increases, and the heat-expandable microcapsule expands. Since the shell becomes thinner due to expansion, if heating is continued further, the heat-expandable agent will leak out of the heat-expandable microcapsule, and the heat-expandable microcapsule will shrink. Therefore, when the foaming agent is subjected to differential scanning calorimetry under heating conditions in the bonding process using a differential scanning calorimeter equipped with a camera, a result such as Figure 3 The expansion ratio-time curve shown has time as the horizontal axis and the expansion ratio of the blowing agent as the vertical axis.

[0039] In addition, in the present disclosure, the adhesive composition contains a thermosetting resin. Therefore, when the adhesive composition is subjected to differential scanning calorimetry under heating conditions in the bonding process, the DSC curve with time as the horizontal axis and heat flow as the vertical axis is, for example, Figure 4 As shown, an exothermic peak due to the curing reaction of the thermosetting resin can be observed.

[0040] Figure 5 The graph is a superposition of the expansion rate-time curve and the DSC curve. The expansion rate-time curve is a curve with time as the horizontal axis and the expansion rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry under heating conditions in the bonding process using a differential scanning calorimeter equipped with a camera. The DSC curve is a curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under heating conditions in the bonding process. Figure 5 As shown, in the expansion rate-time curve 31 for the foaming agent, the slope of the tangent line L1 drawn at the apex of the peak in the curve on the long time side of the peak is set to A. In addition, in the DSC curve 32 for the adhesive composition, the slope of the tangent line L2 drawn at the apex of the exothermic peak in the curve on the long time side of the exothermic peak is set to B. In this case, A<B.

[0041] In the present disclosure, by making A<B, the curing reaction of the thermosetting resin can be advanced before the shrinkage of the foaming agent advances, and the thermosetting resin can be fully cured. Thus, the thickness of the adhesive layer during foaming can be maintained, and the adhesive strength can be improved.

[0042] On the other hand, when A ≥ B, the shrinkage of the foaming agent advances before the curing reaction of the thermosetting resin advances. As a result, the thickness of the adhesive layer during foaming cannot be maintained, and the adhesive strength may decrease.

[0043] Figure 6The graph is obtained by superimposing the expansion ratio-time curve and the DSC curve. The expansion ratio-time curve is a curve with time as the horizontal axis and the expansion ratio of the foaming agent as the vertical axis when the foaming agent is measured by differential scanning calorimetry using a differential scanning calorimeter equipped with a camera. The DSC curve is a curve with time as the horizontal axis and heat flow as the vertical axis when the composition from which the foaming agent is removed is measured by differential scanning calorimetry. Figure 6 As shown, in the expansion rate-time curve 33 for the blowing agent, the time of the peak top is set to T1. In addition, in the DSC curve 34 for the composition from which the blowing agent is removed, the time of the peak top of the exothermic peak is set to T2. In this case, in the bonding process, the adhesive composition is heated so that T1<T2.

[0044] In the present disclosure, in the bonding process, the adhesive composition is heated so that T1 < T2, thereby advancing the expansion of the foaming agent before the curing reaction of the thermosetting resin advances, and the foaming agent can be fully expanded. As a result, the thickness of the adhesive layer during foaming can be increased, and the bonding strength can be improved.

[0045] On the other hand, when T1 ≥ T2, the curing reaction of the thermosetting resin advances before the expansion of the foaming agent. As a result, the expansion of the foaming agent is hindered, the thickness of the adhesive layer during foaming becomes thinner, and the adhesive strength may decrease.

[0046] Thus, in the present disclosure, the adhesive strength can be improved by making the adhesive composition satisfy A<B and heating the adhesive composition so that T1<T2 in the bonding process. Therefore, the reliability and durability of the article obtained by the manufacturing method of the article of the present disclosure can be improved.

[0047] Hereinafter, each step of the method for producing the article of the present disclosure and the adhesive composition will be described.

[0048] 1. Adhesive composition

[0049] The adhesive composition disclosed herein contains a thermosetting resin and a foaming agent. In addition, the foaming agent is a thermally expandable microcapsule.

[0050] (1) Characteristics

[0051] In the adhesive composition of the present disclosure, in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry under heating conditions in the bonding process described later, A is defined as the slope of a tangent line drawn at the apex of the peak in the curve on the long-time side of the peak, and in a DSC curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under heating conditions in the bonding process described later, B is defined as the slope of a tangent line drawn at the apex of the exothermic peak in the curve on the long-time side of the exothermic peak, in which A<B is defined as the slope of a tangent line drawn at the apex of the exothermic peak in the DSC curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under heating conditions in the bonding process described later.

[0052] Here, differential scanning calorimetry (DSC) of the foaming agent was performed using the following method. First, 0.16 mg to 0.17 mg of the foaming agent was weighed in a container. Then, using a differential scanning calorimeter equipped with a camera, the temperature was raised and maintained at a nitrogen flow rate of 20 ml / min and under the heating conditions in the bonding process.

[0053] The camera-equipped differential scanning calorimeter can measure thermal properties while observing changes in the morphology, color, etc. of the sample during the differential scanning calorimetry measurement. In the camera-equipped differential scanning calorimeter, DSC data and image data are synchronized. Therefore, by performing differential scanning calorimetry on the foaming agent using the camera-equipped differential scanning calorimeter, the foaming behavior of the foaming agent can be analyzed. Specifically, first, the area occupied by the foaming agent is obtained based on the image data. At this time, for example, Figure 3 As shown in FIG. 1 , the area occupied by the foaming agent at time 0 in all the image data is set as 0% of the foaming agent expansion ratio, and the area occupied by the foaming agent at the maximum value is set as 100% of the foaming agent expansion ratio. The change in the foaming agent expansion ratio over time is represented as, for example, Figure 3 The expansion ratio-time curve shown is shown. As the differential scanning calorimeter equipped with a camera, for example, "High Sensitivity Differential Scanning Calorimeter DSC7000X" manufactured by Hitachi High TechScience can be used.

[0054] It should be noted that when the foaming agent is subjected to differential scanning calorimetry (DSC), the adhesive composition can be dissolved in a solvent to separate the foaming agent. The solvent is not particularly limited as long as it is a solvent that can dissolve components other than the foaming agent contained in the adhesive composition, and can be appropriately selected according to the type of thermosetting resin contained in the adhesive composition. For example, the solvent used in the adhesive composition can be used. Specifically, methyl ethyl ketone, ethyl acetate, toluene, etc. can be used.

[0055] In the expansion rate-time curve of the foaming agent, a tangent line drawn at the peak apex in the curve on the long-term side of the peak is obtained by the following method. The peak apex is the point where the expansion rate of the foaming agent shows 100%. In addition, in the curve on the long-term side of the peak, the point where the expansion rate of the foaming agent shows 70% is obtained. Thereafter, for example, Figure 5 As shown, a straight line connecting the peak apex (the point where the foaming agent shows a foaming rate of 100%) and the point where the foaming agent shows a foaming rate of 70% in the curve on the long time side of the peak is defined as a tangent line L1 drawn at the peak apex in the curve on the long time side of the peak.

[0056] It should be noted that the peak in the foaming rate-time curve refers to the portion from when the curve leaves the baseline until it returns to the baseline.

[0057] In addition, differential scanning calorimetry (DSC) of the adhesive composition was performed using the following method. First, 5.00 mg to 5.03 mg of the adhesive composition was weighed in a container. Then, the temperature was increased and maintained at a nitrogen flow rate of 20 ml / min and under the heating conditions in the bonding process using a differential scanning calorimeter.

[0058] In addition, when the adhesive composition is subjected to differential scanning calorimetry (DSC), for example, when the adhesive composition contains a solvent, the differential scanning calorimetry is performed after evaporating the solvent.

[0059] In addition, in the DSC curve of the adhesive composition, the tangent line drawn at the apex of the exothermic peak in the curve on the long time side of the exothermic peak is determined by the following method. First, the heat flow at the apex of the exothermic peak is determined. In addition, when the heat flow at the apex of the exothermic peak is set to 100%, the point where the heat flow shows 70% is determined in the curve on the long time side of the exothermic peak. Thereafter, the straight line connecting the apex of the exothermic peak and the point where the heat flow shows 70% in the curve on the long time side of the exothermic peak is set as the tangent line drawn at the apex of the exothermic peak in the curve on the long time side of the exothermic peak. For example, Figure 5 In the graph, when the heat flow hf1 at the top of the exothermic peak is set to 100%, the heat flow hf2 is a point showing 70% of the heat flow hf1. The straight line connecting the top of the exothermic peak (the point showing the heat flow hf1) and the point showing the heat flow hf2 can be set as the tangent line L2 drawn at the top of the exothermic peak in the curve on the long time side of the exothermic peak.

[0060] In addition, in the DSC curve of the adhesive composition, the base line was set to 0.

[0061] The exothermic peak in the DSC curve refers to the portion from when the curve leaves the baseline to when it returns to the baseline.

[0062] In addition, the foaming rate-time curve of the foaming agent and the DSC curve of the adhesive composition are superimposed by the following method to form a curve graph. First, since the horizontal axis is time, the horizontal axis of the foaming rate-time curve of the foaming agent is consistent with the horizontal axis of the DSC curve of the adhesive composition. In addition, with respect to the vertical axis, the position of the baseline in the foaming rate-time curve of the foaming agent is consistent with the position of the baseline in the DSC curve of the adhesive composition. At this time, in the foaming rate-time curve of the foaming agent, the baseline is set to 0. In addition, as described above, in the DSC curve of the adhesive composition, the baseline is set to 0. In addition, with respect to the vertical axis, the position of the apex of the peak in the foaming rate-time curve of the foaming agent (the point where the foaming rate of the foaming agent shows 100%) is consistent with the position of the apex of the exothermic peak in the DSC curve of the adhesive composition. Thus, for example, Figure 5 The graph shown.

[0063] In addition, when the adhesive composition contains multiple foaming agents, at least one foaming agent only needs to satisfy A < B. Among the multiple foaming agents contained in the adhesive composition, it is preferred that the foaming agent with a higher content satisfies A < B. It is particularly preferred that all the multiple foaming agents contained in the adhesive composition satisfy A < B.

[0064] In the expansion rate-time curve of the foaming agent, when there are multiple peaks, at least one peak satisfies A<B. In the expansion rate-time curve, when there are multiple peaks, the adhesive composition generally contains multiple foaming agents. Among them, it is preferred that all peaks satisfy A<B.

[0065] In addition, in the DSC curve of the adhesive composition, when there are multiple exothermic peaks due to the curing reaction of the thermosetting resin, at least one exothermic peak satisfies A<B. In the DSC curve, when there are multiple exothermic peaks due to the curing reaction of the thermosetting resin, for example, the adhesive composition contains multiple thermosetting resins. Among them, it is preferred that the exothermic peak with a small slope B among the multiple exothermic peaks due to the curing reaction of the thermosetting resin satisfies A<B. It is particularly preferred that all the exothermic peaks satisfy A<B.

[0066] In the adhesive composition, A<B. Among them, it is preferred that B is much larger than A. When the slope B is large, the curing speed of the thermosetting resin becomes faster. In addition, when the slope A is small, the shrinking speed of the foaming agent becomes slower. Therefore, when B is much larger than A, the thermosetting resin can be fully cured before the shrinkage of the foaming agent proceeds, and the bonding strength can be improved.

[0067] In the adhesive composition, for example, the slope A can be controlled by adjusting the thickness of the shell of the heat-expandable microcapsule as the foaming agent. Specifically, if the thickness of the shell of the heat-expandable microcapsule is thick, the slope A tends to be small. On the other hand, if the thickness of the shell of the heat-expandable microcapsule is thin, the slope A tends to be large.

[0068] In addition, in the adhesive composition, for example, the slope B can be controlled by adjusting the composition of the adhesive composition. For example, when the adhesive composition further contains a curing agent, there is a tendency for the slope B to become larger. In addition, for example, when the adhesive composition further contains a curing agent and a curing catalyst, there is a tendency for the slope B to become larger. In addition, for example, when the adhesive composition contains a multifunctional thermosetting resin, there is a tendency for the slope B to become larger.

[0069] In addition, in the expansion ratio-time curve of the foaming agent, the time from the peak top (the point where the expansion ratio of the foaming agent shows 100%) to the shrinkage stabilization of the foaming agent is, for example, 0.5 minutes to 60 minutes, or 1 minute to 45 minutes. If the above time is too short, the slope A becomes large, and A<B may not be satisfied. In addition, if the above time is too long, the foaming ratio of the foaming agent may decrease.

[0070] In addition, in the DSC curve of the adhesive composition, the time from the apex of the exothermic peak to the baseline is, for example, 0.1 minutes to 30 minutes, 0.2 minutes to 10 minutes, or 0.3 minutes to 5 minutes. If the above time is too long, the slope B becomes smaller and A<B may not be satisfied. In addition, if the above time is too short, the storage stability may be reduced.

[0071] As described later, in the present disclosure, when a foamable adhesive sheet is used and the foamable adhesive sheet has a first adhesive layer and a second adhesive layer, as long as the adhesive composition contained in at least one adhesive layer among the first adhesive layer and the second adhesive layer contains a foaming agent. In the case where only the adhesive composition contained in one adhesive layer among the first adhesive layer and the second adhesive layer contains a foaming agent, as long as the adhesive composition containing the foaming agent satisfies the above-mentioned characteristics. In addition, in the case where both the adhesive composition contained in the first adhesive layer and the adhesive composition contained in the second adhesive layer contain a foaming agent, as long as the adhesive composition contained in at least one adhesive layer satisfies the above-mentioned characteristics. Among them, it is preferred that the adhesive composition contained in the two adhesive layers of the first adhesive layer and the second adhesive layer satisfies the above-mentioned characteristics.

[0072] (2) Composition

[0073] The adhesive composition disclosed herein contains a thermosetting resin and a foaming agent. In addition, the foaming agent is a thermally expandable microcapsule.

[0074] (a) Foaming agent

[0075] The foaming agent is a heat-expandable microcapsule. As the foaming agent, heat-expandable microcapsules generally used in adhesive compositions can be used.

[0076] The heat-expandable microcapsules preferably have a heat-expanding agent such as hydrocarbon as a core and a resin such as an acrylonitrile copolymer as a shell.

[0077] The foaming agent may be used alone or in combination of two or more.

[0078] The foaming start temperature of the foaming agent is preferably above the softening temperature of the thermosetting resin and below the activation temperature of the curing reaction of the thermosetting resin. The foaming start temperature of the foaming agent is, for example, above 70°C, and may be above 100°C. If the foaming start temperature is too low, the foaming starts prematurely, and the foaming occurs in a state where the softness and fluidity of the resin component are low, and it may be difficult to produce uniform foaming. On the other hand, the foaming start temperature of the foaming agent is, for example, below 210°C. If the foaming start temperature is too high, the resin component may deteriorate.

[0079] The softening temperature of the thermosetting resin can be measured by the ring and ball softening temperature test method specified in JIS K7234.

[0080] The average particle size of the foaming agent may be, for example, 10 μm or more, 13 μm or more, or 17 μm or more. In addition, the average particle size of the foaming agent is preferably less than the thickness of the adhesive layer, for example, 44 μm or less, 30 μm or less, or 24 μm or less.

[0081] It should be noted that the average particle size of the foaming agent is the particle size at the cumulative value of 50% in the particle size distribution obtained by laser diffraction scattering method. In addition, when measuring the average particle size of the foaming agent, the adhesive composition is dissolved in a solvent to separate the foaming agent. The solvent is not particularly limited as long as it can dissolve the components other than the foaming agent contained in the adhesive composition, and can be appropriately selected according to the type of thermosetting resin contained in the adhesive composition. For example, the solvent used in the adhesive composition can be used. Specifically, methyl ethyl ketone, ethyl acetate, toluene, etc. can be used.

[0082] The expansion ratio at the maximum foaming temperature of the foaming agent is, for example, 1.5 times or more, or 3 times or more. On the other hand, the expansion ratio at the maximum foaming temperature of the foaming agent is, for example, 15 times or less, or 10 times or less.

[0083] Regarding the content of the foaming agent, when the resin component contained in the adhesive composition is set to 100 parts by mass, it is, for example, 0.5 parts by mass or more, or 2 parts by mass or more, or 3 parts by mass or more, or 4 parts by mass or more, or 5 parts by mass or more. On the other hand, the content of the foaming agent is, for example, 25 parts by mass or less, or 20 parts by mass or less, or 15 parts by mass or less relative to 100 parts by mass of the resin component contained in the adhesive composition.

[0084] (b) Thermosetting resin

[0085] As the thermosetting resin, a thermosetting resin generally used in an adhesive composition can be used. The thermosetting resin can be applied even when the first member and the second member are not transparent, such as metal members.

[0086] Examples of the thermosetting resin include epoxy resins, acrylic resins, phenolic resins, unsaturated polyester resins, alkyd resins, urethane resins, and thermosetting polyimide resins.

[0087] Among them, epoxy resin is preferred. In this case, the adhesive composition preferably contains epoxy resin as a thermosetting resin, a curing agent and a foaming agent. Generally speaking, the adhesive composition containing epoxy resin has excellent mechanical strength, heat resistance, insulation, chemical resistance, etc., has small curing shrinkage, and can be used for a wide range of purposes.

[0088] Hereinafter, epoxy resin will be described by way of example.

[0089] (Epoxy resin)

[0090] The epoxy resin disclosed herein is a compound having at least one epoxy group or glycidyl group, and curing after cross-linking polymerization reaction by using a curing agent in combination. The epoxy resin also includes a monomer having at least one epoxy group or glycidyl group.

[0091] As epoxy resin, for example, aromatic epoxy resin, aliphatic epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin can be enumerated. As the specific example of epoxy resin, bisphenol-type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol A linear novolac epoxy resin, cresol linear novolac epoxy resin, modified epoxy resins such as linear novolac epoxy resin, carbamate modified epoxy resin, rubber modified epoxy resin can be enumerated. In addition, as other specific examples, biphenyl type epoxy resin, stilbene type epoxy resin, trisphenol methane type epoxy resin, alkyl modified trisphenol methane type epoxy resin, epoxy resin containing triazine core, dicyclopentadiene modified phenol type epoxy resin, naphthalene type epoxy resin, glycol type epoxy resin, pentaerythritol type epoxy resin can be enumerated. Epoxy resin can be 1 kind, can also be 2 kinds or more.

[0092] Bisphenol A epoxy resin can exist in a liquid state at room temperature or a solid state at room temperature according to the number of repeating units of the bisphenol skeleton. Bisphenol A epoxy resin having a main chain bisphenol skeleton of, for example, 2 or more and 10 or less is solid at room temperature. In particular, bisphenol A epoxy resin can achieve improved heat resistance, and is therefore preferred from this point of view.

[0093] The epoxy resin may be a monofunctional epoxy resin, a difunctional epoxy resin, a trifunctional epoxy resin, or a tetrafunctional or higher-functional epoxy resin.

[0094] (c) Acrylic resin

[0095] In the present disclosure, when the adhesive composition contains epoxy resin as a thermosetting resin, it can further contain an acrylic resin compatible with epoxy resin. Acrylic resin is a resin compatible with epoxy resin. Since acrylic resin is compatible with epoxy resin, it is easy to improve the toughness of the adhesive layer. As a result, the adhesion after foaming and curing can be improved. In addition, it can be considered that acrylic resin plays a role as a compatibilizer of a foaming agent (for example, a foaming agent of a resin of acrylonitrile copolymer in the shell), uniformly disperses and foams, thereby improving the adhesion after foaming and curing. In addition, the flexibility caused by acrylic resin is brought into play, and the improvement of the adhesion to the substrate after foaming and curing and the crack resistance after foaming and curing can be achieved. In addition, acrylic resin is compatible with epoxy resin, and the hardness of the surface of the adhesive layer can be kept high. On the other hand, if acrylic resin is incompatible with epoxy resin, a soft part is formed on the surface of the adhesive layer, so the interface with the first component and the second component is not easy to be smooth, and there is a situation where workability is reduced.

[0096] The acrylic resin disclosed in the present invention is compatible with the epoxy resin. Here, for the compatibility of the acrylic resin and the epoxy resin, for example, an adhesive layer can be made using an adhesive composition, and when the cross-section of the adhesive layer is observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), it is confirmed by whether micron-sized islands are generated. More specifically, the average particle size of the island is preferably less than 1 μm. Among them, the average particle size of the island can also be less than 0.5 μm, or less than 0.3 μm. The number of samples is preferably large, for example, more than 100. The area of ​​the observed region is in the range of 100 μm×100 μm, or when the thickness of the adhesive layer is less than 100 μm, it is carried out in the range of thickness×100 μm.

[0097] The acrylic resin may have a polar group. Examples of the polar group include an epoxy group, a hydroxyl group, a carboxyl group, a nitrile group, and an amide group.

[0098] The acrylic resin may be a mixed component comprising two or more homopolymers, or a component comprising one or more copolymers, wherein the homopolymer is a homopolymer of an acrylate monomer, and the copolymer is a copolymer of two or more acrylate monomers. In addition, the acrylic resin may be a mixed component of the homopolymer and the copolymer. The "acrylic acid" of the acrylate monomer also includes the concept of methacrylic acid. Specifically, the acrylic resin may be a mixture of a methacrylate polymer and an acrylate polymer, or may be an acrylate polymer such as acrylate-acrylate, methacrylate-methacrylate, or methacrylate-acrylate. Among them, the acrylic resin preferably comprises a copolymer of two or more acrylate monomers (a (meth) acrylate copolymer).

[0099] As the monomer components constituting the (meth)acrylate copolymer, for example, the monomer components described in Japanese Patent Publication No. 2014-065889 can be cited. The above-mentioned monomer components may have the above-mentioned polar groups. As the above-mentioned (meth)acrylate copolymer, for example, ethyl acrylate-butyl acrylate-acrylonitrile copolymer, ethyl acrylate-acrylonitrile copolymer, butyl acrylate-acrylonitrile copolymer can be cited. It should be noted that "acrylic acid" such as methyl acrylate and ethyl acrylate also includes "methacrylic acid" such as methyl methacrylate and ethyl methacrylate.

[0100] As the (meth)acrylate copolymer, a block copolymer is preferred, and an acrylic block copolymer such as a methacrylate-acrylate copolymer is more preferred. Examples of the (meth)acrylate constituting the acrylic block copolymer include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, and benzyl acrylate. These "acrylic acids" also include "methacrylic acids".

[0101] Specific examples of methacrylate-acrylate copolymers include acrylic copolymers such as methyl methacrylate-butyl acrylate-methyl methacrylate (MMA-BA-MMA) copolymers, and MMA-BA-MMA copolymers also include block copolymers of polymethyl methacrylate-polybutyl acrylate-polymethyl methacrylate (PMMA-PBA-PMMA).

[0102] The acrylic copolymer may not have a polar group, or may be a modified product in which the polar group is partially introduced. The modified product is easily compatible with the epoxy resin, so the adhesiveness is further improved.

[0103] Among them, the acrylic resin is preferably a (meth)acrylate copolymer having a first polymer part having a glass transition temperature (Tg) of 10°C or less and a second polymer part having a glass transition temperature (Tg) of 20°C or more. Such a (meth)acrylate copolymer has a first polymer part that becomes a soft segment and a second polymer part that becomes a hard segment. By adding such a copolymer, the toughness of the adhesive layer after curing is improved, and the adhesive force can be further improved.

[0104] The above effects can be inferred as follows: By using an acrylic resin having both a soft segment and a hard segment such as the above-mentioned (meth)acrylate copolymer, since the hard segment contributes to heat resistance and the soft segment contributes to toughness and flexibility, an adhesive layer having excellent heat resistance, toughness and flexibility can be obtained.

[0105] At least one of the first polymer part and the second polymer part contained in the (meth)acrylate copolymer is compatible with the epoxy resin. When the first polymer part is compatible with the epoxy resin, the flexibility can be improved. In addition, when the second polymer part is compatible with the epoxy resin, the cohesion and toughness can be improved.

[0106] The (meth)acrylate copolymer is particularly preferably a block copolymer, and particularly preferably an ABA block copolymer in which the compatible portion is a polymer block A and the incompatible portion is a polymer block B. More preferably, it is an ABA block copolymer in which the first polymer portion is an incompatible portion, the second polymer portion is a compatible portion, the first polymer portion is a polymer block B, and the second polymer portion is a polymer block A.

[0107] Furthermore, the (meth)acrylate copolymer may be a modified product in which the polar group is introduced into a part of the first polymer portion or the second polymer portion.

[0108] Specific examples of the (meth)acrylate copolymer having the first polymer part and the second polymer part include the above-mentioned MMA-BA-MMA copolymer.

[0109] About the content of acrylic resin, when the resin component contained in the adhesive composition is set to 100 mass parts, for example, it is more than 1 mass part, it can also be more than 3 mass parts, it can also be more than 5 mass parts, it can also be more than 7 mass parts, it can also be more than 10 mass parts. If the content of acrylic resin is too little, the adhesion after foaming and curing and the adhesion of the adhesive layer to the substrate are likely to be reduced. On the other hand, about the content of acrylic resin, when the resin component contained in the adhesive composition is set to 100 mass parts, for example, it is less than 60 mass parts, it can also be less than 50 mass parts, it can also be less than 40 mass parts, it can also be less than 35 mass parts, it can also be less than 30 mass parts. If the content of acrylic resin is too much, the film strength is likely to be reduced.

[0110] (d) Curing agent

[0111] The adhesive composition of the present disclosure may further contain a curing agent.

[0112] When the adhesive composition contains an epoxy resin as the thermosetting resin, a curing agent generally used in epoxy resin adhesives can be used as the curing agent.

[0113] The curing agent is preferably solid at 23°C. A curing agent that is solid at 23°C can improve storage stability (usable time) compared to a curing agent that is liquid at 23°C. In addition, the curing agent may also be a latent curing agent. In addition, the curing agent is generally a curing agent that produces a curing reaction due to heat. In addition, the curing agent may be used alone or in combination of two or more.

[0114] The reaction start temperature of the curing agent is, for example, above 110°C, and may also be above 130°C. If the reaction start temperature is too low, the reaction is started prematurely, and curing occurs in a state where the softness and fluidity of the resin component are low, and it may be difficult to produce uniform curing. On the other hand, the reaction start temperature of the curing agent is, for example, below 200°C. If the reaction start temperature is too high, the resin component may deteriorate. It should be noted that when a resin with high heat resistance such as a phenolic resin is used in addition to the epoxy resin, the reaction start temperature of the curing agent may be, for example, below 300°C because the resin component deteriorates less. The reaction start temperature of the curing agent can be determined using differential scanning calorimetry (DSC).

[0115] Specific examples of the curing agent include imidazole-based curing agents, phenol-based curing agents, amine-based curing agents, acid anhydride-based curing agents, isocyanate-based curing agents, and thiol-based curing agents.

[0116] As imidazole curing agents, for example, imidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-phenylimidazole, carboxylates of imidazole compounds, and adducts with epoxy compounds can be cited. In addition, the imidazole curing agent preferably has a hydroxyl group. Since crystallization occurs through hydrogen bonding between hydroxyl groups, there is a tendency for the reaction start temperature to become higher.

[0117] As the phenolic curing agent, for example, phenolic resin can be mentioned. In addition, as the phenolic resin, for example, resol type phenolic resin and novolac type phenolic resin can be mentioned. From the viewpoints of adhesion to the substrate after foaming and curing, crack resistance after foaming and curing, etc., phenolic novolac resin with a Tg of less than 110°C is particularly preferred. In addition, a phenolic curing agent and an imidazole curing agent can also be used in combination. In this case, it is preferred to use an imidazole curing agent as a curing catalyst.

[0118] Examples of amine curing agents include aliphatic amines such as diethylenetriamine (DETA), triethylenetetramine (TETA), and meta-xylylenediamine (MXDA); aromatic amines such as diaminodiphenylmethane (DDM), meta-phenylenediamine (MPDA), and diaminodiphenylsulfone (DDS); alicyclic amines; and polyamide amines. In addition, dicyandiamide curing agents such as dicyandiamide (DICY), organic acid dihydrazide curing agents, amine adduct curing agents, and ketimine curing agents can be used as amine curing agents.

[0119] Examples of the acid anhydride curing agent include alicyclic acid anhydrides (liquid acid anhydrides) such as hexahydrophthalic anhydride (HHPA) and methyltetrahydrophthalic anhydride (MTHPA); and aromatic acid anhydrides such as trimellitic anhydride (TMA), pyromellitic anhydride (PMDA), and benzophenonetetracarboxylic dianhydride (BTDA).

[0120] As an isocyanate type curing agent, blocked isocyanate is mentioned, for example.

[0121] Examples of the thiol-based curing agent include ester bond type thiol compounds, aliphatic ether bond type thiol compounds, and aromatic ether bond type thiol compounds.

[0122] Among them, it is preferred to use a curing agent other than the imidazole curing agent in combination with the imidazole curing agent. In this case, it is preferred to use the imidazole curing agent as a curing catalyst.

[0123] About the content of curing agent, when the resin component contained in the adhesive composition is set to 100 mass parts, for example, more than 1 mass part and less than 40 mass parts. For example, when the imidazole curing agent as a curing agent is used as the main component, about the content of curing agent, when the resin component contained in the adhesive composition is set to 100 mass parts, for example, preferably more than 1 mass part and less than 15 mass parts. On the other hand, when the phenol curing agent as a curing agent is used as the main component, about the content of curing agent, when the resin component contained in the adhesive composition is set to 100 mass parts, for example, preferably more than 5 mass parts and less than 40 mass parts. It should be noted that the so-called imidazole curing agent or phenol curing agent as a curing agent is used as the main component, which means that the mass ratio of imidazole curing agent or phenol curing agent in the curing agent is the largest.

[0124] (e) Other ingredients

[0125] In the adhesive composition of the present disclosure, for example, when the thermosetting resin is an epoxy resin, the adhesive composition may contain only the above-mentioned epoxy resin and acrylic resin as resin components, or may further contain other resins. Examples of other resins include urethane resins.

[0126] The total ratio of the epoxy resin and the acrylic resin to the resin component contained in the adhesive composition may be, for example, 70 mass % or more, 80 mass % or more, 90 mass % or more, or 100 mass %.

[0127] The content of the resin component contained in the adhesive composition may be, for example, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more.

[0128] The adhesive composition may contain additives such as silane coupling agents, fillers, antioxidants, light stabilizers, ultraviolet absorbers, lubricants, plasticizers, antistatic agents, crosslinking agents, colorants, etc. as needed. As silane coupling agents, for example, epoxy silane coupling agents can be mentioned. As fillers, for example, inorganic fillers such as calcium carbonate, aluminum hydroxide, magnesium hydroxide, antimony trioxide, zinc borate, molybdenum compounds, titanium dioxide can be mentioned. As antioxidants, for example, phenolic antioxidants and sulfur antioxidants can be mentioned.

[0129] The adhesive composition may contain a solvent or may not contain a solvent. It should be noted that the solvent in this specification includes not only a strict solvent (a solvent that dissolves a solute) but also a broad meaning of a dispersion medium. In addition, the solvent contained in the adhesive composition is volatilized and removed when the adhesive composition is applied and dried to form an adhesive layer.

[0130] (3) Preparation method

[0131] The adhesive composition can be obtained by mixing the above-mentioned components and kneading and dispersing as needed. As the mixing and dispersing method, a common kneading disperser can be used, such as a double-roll mill, a triple-roll mill, a gravel mill, a Tron mill, a Szegvari mill, a high-speed impeller disperser, a high-speed stone mill, a high-speed impact mill, a disperser, a high-speed mixer, a ribbon blender, a continuous kneader, a strong kneading machine, a tumble mixer, a blender, a disperser, a homogenizer, and an ultrasonic disperser.

[0132] 2. Configuration process

[0133] The placement step of the present disclosure is a step of placing the adhesive composition between the first member and the second member.

[0134] When the adhesive composition is arranged between the first member and the second member, for example, a foamable adhesive sheet having an adhesive layer containing the adhesive composition can be used, and the foamable adhesive sheet can be arranged between the first member and the second member. In addition, for example, a liquid adhesive composition can also be used, and the liquid adhesive composition can be applied to the surface of at least one of the first member and the second member. Among them, it is preferred to use a foamable adhesive sheet and arrange the foamable adhesive sheet between the first member and the second member. The foamable adhesive sheet is excellent in operability and workability.

[0135] When a foamable adhesive sheet is used, the foamable adhesive sheet may, for example, have only an adhesive layer containing an adhesive composition, or may have a first adhesive layer containing an adhesive composition and a second adhesive layer containing an adhesive composition, or may have a first adhesive layer containing an adhesive composition, a substrate, and a second adhesive layer containing an adhesive composition in this order.

[0136] In addition, the foamable adhesive sheet will be described later.

[0137] In addition, when a foamable adhesive sheet is used, the method of arranging the foamable adhesive sheet between the first member and the second member can be appropriately selected according to the types of the first member and the second member. For example, there can be a method of arranging a foamable adhesive sheet on one of the first member and the second member and arranging the other member on the opposite side of the foamable adhesive sheet to the one member; a method of inserting the foamable adhesive sheet into the gap between the first member and the second member; a method of arranging the foamable adhesive sheet in the hole, groove, etc. of the first member and inserting the second member into the gap after the foamable adhesive sheet is arranged in the hole, groove, etc. of the first member, etc. In addition, for example, when the first member has a hole or groove and the second member is arranged in the hole or groove of the first member for bonding, there can be a method of arranging the second member with the foamable adhesive sheet attached to the hole or groove of the first member after the foamable adhesive sheet is attached to the second member; a method of arranging the second member in the hole or groove of the first member after the foamable adhesive sheet is attached to the hole or groove of the first member, etc.

[0138] In addition, when a liquid adhesive composition is used, the method of arranging the liquid adhesive composition between the first member and the second member can be appropriately selected according to the types of the first member and the second member. For example, a method of applying a liquid adhesive composition to one of the first member and the second member and arranging the other member on the coating film of the liquid adhesive composition can be cited; a method of injecting a liquid adhesive composition into the gap between the first member and the second member; a method of applying a liquid adhesive composition to the hole, groove, etc. of the first member and inserting the second member into the gap after applying the liquid adhesive composition to the hole, groove, etc. of the first member, etc. In addition, for example, in the case where the first member has a hole or groove and the second member is arranged in the hole or groove of the first member for bonding, a method of applying a liquid adhesive composition to the second member and arranging the second member coated with the liquid adhesive composition in the hole or groove of the first member can be cited; a method of applying a liquid adhesive composition to the hole or groove of the first member and arranging the second member in the hole or groove of the first member coated with the liquid adhesive composition can be cited.

[0139] The coating method of the liquid adhesive composition is not particularly limited, and examples thereof include roller coating, reverse roll coating, transfer roll coating, gravure coating, gravure reverse coating, comma blade coating, rod coating, blade coating, rod coating, wire rod coating, die coating, die lip coating, and dip coating.

[0140] 3. Bonding process

[0141] The bonding step of the present disclosure is a step of heating the adhesive composition to foam and cure it to bond the first member and the second member.

[0142] In the present disclosure, in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when differential scanning calorimetry is performed on the foaming agent using a differential scanning calorimeter equipped with a camera, the time of the peak apex is set to T1, and in a DSC curve with time as the horizontal axis and heat flow as the vertical axis when differential scanning calorimetry is performed on a composition obtained by removing the foaming agent from the adhesive composition, the time of the peak of the exothermic peak is set to T2. In this case, in the bonding step, the adhesive composition is heated so that T1<T2.

[0143] Here, differential scanning calorimetry (DSC) of the blowing agent is performed using the following method. First, 0.16 mg to 0.17 mg of the blowing agent is weighed in a container. Then, using a differential scanning calorimeter equipped with a camera, the temperature is increased and maintained at a nitrogen flow rate of 20 ml / min and at a given temperature increase rate, heating temperature, holding time, and temperature increase rate.

[0144] In addition, the differential scanning calorimetry (DSC) of the composition from which the foaming agent is removed from the adhesive composition is performed using the following method. First, 5.00 mg to 5.03 mg of the composition from which the foaming agent is removed is weighed in a container. Then, using a differential scanning calorimeter, the temperature is increased and maintained at a nitrogen flow rate of 20 ml / min and at a given heating rate, heating temperature, holding time, and heating rate. At this time, the heating conditions are set to be the same in the differential scanning calorimetry (DSC) of the foaming agent and the differential scanning calorimetry (DSC) of the composition from which the foaming agent is removed from the adhesive composition.

[0145] In addition, the expansion rate-time curve of the foaming agent and the DSC curve of the composition from which the foaming agent is removed are superimposed by the following method to form a single graph. Since the horizontal axis is time, the horizontal axis of the expansion rate-time curve of the foaming agent is consistent with the horizontal axis of the DSC curve of the composition from which the foaming agent is removed. Thus, for example, Figure 6 The graph shown.

[0146] In addition, when the adhesive composition contains multiple foaming agents, at least one foaming agent satisfies T1<T2. Among the multiple foaming agents contained in the adhesive composition, it is preferred that the foaming agent with a higher content satisfies T1<T2. It is particularly preferred that all the multiple foaming agents contained in the adhesive composition satisfy T1<T2.

[0147] In the case where there are multiple peaks in the expansion rate-time curve of the foaming agent, at least one peak satisfies T1<T2. In the case where there are multiple peaks in the expansion rate-time curve, the adhesive composition generally contains multiple foaming agents. Among them, it is preferred that all peaks satisfy T1<T2.

[0148] When the adhesive composition contains a plurality of thermosetting resins, it is preferred that all of the plurality of thermosetting resins contained in the adhesive composition satisfy T1<T2.

[0149] In the DSC curve of the adhesive composition obtained by removing the foaming agent from the adhesive composition, when there are a plurality of exothermic peaks due to the curing reaction of the thermosetting resin, it is preferred that all of the exothermic peaks satisfy T1<T2.

[0150] In the bonding step, the adhesive composition is heated so that T1<T2.

[0151] In the bonding process, for example, the time T1 of the peak in the expansion rate-time curve of the foaming agent and the time T2 of the peak of the exothermic peak in the DSC curve of the composition from which the foaming agent is removed can be controlled by adjusting the heating time from room temperature to the heating temperature. Specifically, if the heating time from room temperature to the heating temperature is short, T1 tends to be on the short side relative to T2. On the other hand, if the heating time from room temperature to the heating temperature is long, T1 tends to be on the long side relative to T2.

[0152] In addition, the heating temperature in the bonding process is preferably within the range of ±40°C of the maximum foaming temperature of the foaming agent, more preferably within the range of ±30°C of the maximum foaming temperature of the foaming agent, and further preferably within the range of ±20°C of the maximum foaming temperature of the foaming agent. If the heating temperature is higher than the above range, even if the thermosetting resin is cured, the thickness of the adhesive layer during foaming cannot be maintained due to the shrinkage of the foaming agent, and the bonding strength may be reduced. On the other hand, if the heating temperature is lower than the above range, the expansion of the foaming agent is insufficient, and the bonding strength may be reduced. In this case, interface damage may easily occur between the adhesive composition after foaming and curing and the first component or the second component.

[0153] It should be noted that the maximum foaming temperature of the foaming agent refers to the temperature at the top of the peak in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry using a differential scanning calorimeter equipped with a camera. In this case, the heating conditions in the differential scanning calorimetry can be set to a heating rate of 31°C / min, for example.

[0154] In addition, in the bonding process, the heating time from room temperature to the heating temperature is, for example, 0.1 minutes to 60 minutes, 0.3 minutes to 45 minutes, or 0.5 minutes to 30 minutes. If the heating time is too short, the heating speed becomes faster, overshoot occurs, and the deviation from the target temperature may become larger. On the other hand, if the heating time is too long, T1<T2 may not be satisfied.

[0155] In addition, in the bonding process, the holding time at the heating temperature is, for example, 0.5 minutes to 240 minutes, or 1 minute to 120 minutes, or 2 minutes to 60 minutes. When the heating temperature is high and the holding time is long, even if the thermosetting resin is cured, the foaming agent shrinks and the thickness of the adhesive layer during foaming cannot be maintained, and the bonding strength may be reduced.

[0156] 4. Foam adhesive sheet

[0157] The foamable adhesive sheet disclosed in the present invention has at least an adhesive layer containing the above-mentioned adhesive composition.

[0158] In addition, the foamable adhesive sheet can only have an adhesive layer, can also have the first adhesive layer and the second adhesive layer, and can also have the first adhesive layer, substrate and the second adhesive layer in sequence. When the substrate is configured between the first adhesive layer and the second adhesive layer, the operability and workability of the foamable adhesive sheet can be made good. On the other hand, when the foamable adhesive sheet does not have a substrate, the thickness of the foamable adhesive sheet as a whole can be thinned. Thus, for example, even if the gap is narrow, the foamable adhesive sheet can be inserted.

[0159] For example Figure 2 The foamable adhesive sheet 10 shown has only the adhesive layer 1. In addition, for example Figure 7 The foamable adhesive sheet 10 shown includes a first adhesive layer 1 a , a substrate 2 , and a second adhesive layer 1 b in this order.

[0160] (1) Adhesive layer

[0161] The adhesive layer contains the above-mentioned adhesive composition.

[0162] The thickness of the adhesive layer is not particularly limited, but is preferably above the average particle size of the foaming agent, for example, above 10 μm, or above 15 μm, or above 20 μm. If the adhesive layer is too thin, it is possible that the adhesion to the substrate and the adhesion after foaming and curing cannot be fully obtained. On the other hand, the thickness of the adhesive layer is, for example, below 200 μm, or below 150 μm, or below 100 μm. If the adhesive layer is too thick, the surface quality is likely to deteriorate.

[0163] Here, the thickness of the adhesive layer is a value measured based on a cross section of the foamable adhesive sheet in the thickness direction observed by a transmission electron microscope (TEM), a scanning electron microscope (SEM) or a scanning transmission electron microscope (STEM), and can be set as the average value of the thickness of 10 randomly selected locations. It should be noted that the thickness of other layers of the foamable adhesive sheet can also be measured in the same manner.

[0164] The adhesive layer may be a continuous layer or a discontinuous layer. As the discontinuous layer, for example, patterns such as stripes and dots may be cited. In addition, the surface of the adhesive layer may have a concave-convex shape such as a print.

[0165] The adhesive layer can be formed, for example, by applying the above-mentioned adhesive composition and removing the solvent. Examples of the coating method include roll coating, reverse roll coating, transfer roll coating, gravure coating, gravure reverse coating, comma blade coating, rod coating, blade coating, rod coating, wire rod coating, die coating, die lip coating, and dip coating.

[0166] (2) Base material

[0167] The substrate preferably has insulating properties. In addition, the substrate is preferably in sheet form. The substrate may have a single-layer structure or a multi-layer structure. In addition, the substrate may or may not have a porous structure inside.

[0168] Examples of the substrate include a resin substrate and a nonwoven fabric.

[0169] As the resin contained in the resin substrate, for example, polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate (PEN), and aromatic polyesters; polycarbonate; polyarylate; polyurethane; polyamide resins such as polyamide and polyether amide; polyimide resins such as polyimide, polyether imide, and polyamide-imide; polysulfone resins such as polysulfone and polyether sulfone; polyether ketone resins such as polyether ketone and polyether ether ketone; polyphenylene sulfide (PPS); modified polyphenylene ether, etc. The glass transition temperature of the resin is, for example, above 80°C, and may be above 140°C, or may be above 200°C. In addition, a liquid crystal polymer (LCP) may be used as the resin.

[0170] Examples of the nonwoven fabric include nonwoven fabrics containing fibers such as cellulose fibers, polyester fibers, nylon fibers, aramid fibers, polyphenylene sulfide fibers, liquid crystal polymer fibers, glass fibers, metal fibers, and carbon fibers.

[0171] In order to improve the adhesion with the adhesive layer, the substrate may be subjected to a surface treatment.

[0172] The average thickness of the substrate is not particularly limited, and may be, for example, 2 μm or more, 5 μm or more, or 9 μm or more. Also, the average thickness of the substrate may be, for example, 200 μm or less, 100 μm or less, or 50 μm or less.

[0173] (3) Other components

[0174] The foamable adhesive sheet of the present disclosure may have other configurations as necessary in addition to the above-mentioned adhesive layer and substrate.

[0175] (a) Middle layer

[0176] The disclosed foamable adhesive sheet can have an intermediate layer between substrate and adhesive layer. By configuring the intermediate layer, the adhesion of adhesive layer to substrate can be improved. In addition, by configuring the intermediate layer, for example, when bending the foamable adhesive sheet, the stress applied to the bending portion can be relieved, or when cutting the foamable adhesive sheet, the stress applied to the cutting portion can be relieved. As a result, when bending the foamable adhesive sheet, when cutting, the adhesive layer can be suppressed from floating and peeling of the substrate.

[0177] For example, in Figure 8 In the foamable adhesive sheet 10 shown, a first intermediate layer 3a is disposed between the substrate 2 and the first adhesive layer 1a, and a second intermediate layer 3b is disposed between the substrate 2 and the second adhesive layer 1b. Figure 8 In the embodiment, the foamable adhesive sheet 10 includes both the first intermediate layer 3a and the second intermediate layer 3b, but may include only one of them.

[0178] The material contained in the intermediate layer is not particularly limited as long as it can improve the adhesion between the substrate and the adhesive layer and can relieve stress, and can be appropriately selected according to the materials of the substrate and the adhesive layer, etc. For example, polyester, polyvinyl chloride, polyvinyl acetate, polyurethane, polymers obtained by copolymerizing at least two or more of them, their crosslinked products, and their mixtures, etc. can be cited.

[0179] The crosslinked product is a crosslinked product obtained by crosslinking the above-mentioned resin using a curing agent. As the curing agent, for example, an isocyanate curing agent can be cited. In addition, for example, when the reactive group / NCO equivalent is set to 1, it is preferred to add the isocyanate curing agent at a ratio of 0.5 mass % or more and 20 mass % or less relative to the resin.

[0180] The intermediate layer preferably contains a cross-linked resin. It should be noted that the so-called cross-linked resin refers to a resin that does not melt even when it is exposed to high temperatures. This can improve the adhesive force at high temperatures, that is, the heat resistance.

[0181] The thickness of the middle layer is not particularly limited, but for example, more than 0.1 μm, more than 0.5 μm, or more than 1 μm. If the middle layer is too thin, it is possible to fully obtain the effect of the adhesive layer from the base material peeling when suppressing the bending of the foaming adhesive sheet and when cutting. On the other hand, the thickness of the middle layer is, for example, less than 4 μm, or less than 3.5 μm. The middle layer itself is usually not high in heat resistance, so if the middle layer is too thick, the heat resistance (adhesion under high temperature) is likely to decrease.

[0182] The intermediate layer can be formed, for example, by applying the resin composition and removing the solvent. Examples of the coating method include roll coating, reverse roll coating, transfer roll coating, gravure coating, gravure reverse coating, comma blade coating, rod coating, blade coating, rod coating, wire rod coating, die coating, die lip coating, and dip coating.

[0183] (4) Foam adhesive sheet

[0184] The thickness of the foamable adhesive sheet of the present disclosure is, for example, 10 μm or more, or 20 μm or more. On the other hand, the thickness of the foamable adhesive sheet is, for example, 1000 μm or less, or 200 μm or less.

[0185] (5) Method for manufacturing foamable adhesive sheet

[0186] The manufacturing method of the foamable adhesive sheet of the present disclosure is not particularly limited. For example, when the foamable adhesive sheet does not have a substrate, a method for peeling the spacer from the adhesive layer after applying the above-mentioned adhesive composition on one side of the spacer and drying to form an adhesive layer can be cited. In addition, for example, when the foamable adhesive sheet has the first adhesive layer, the substrate and the second adhesive layer in sequence, a method for forming the first adhesive layer and the second adhesive layer by applying the above-mentioned adhesive composition on both sides of the substrate and drying can be cited. The first adhesive layer and the second adhesive layer can be formed in sequence or simultaneously. In addition, for example, a method for forming the first adhesive layer by applying the above-mentioned adhesive composition on one side of the substrate and drying, forming the second adhesive layer by applying the above-mentioned adhesive composition on one side of the spacer and drying, and laminating the second adhesive layer and the spacer on the other side of the substrate can also be cited.

[0187] 5. First component and second component

[0188] The first member and the second member of the present disclosure can be appropriately selected according to the purpose of the article, etc. The first member and the second member are preferably members that require bonding and insulation. For example, they can be parts of electrical and electronic equipment.

[0189] B. Adhesive Composition

[0190] The adhesive composition disclosed herein contains a thermosetting resin and a foaming agent, wherein the foaming agent is a heat-expandable microcapsule, and in a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry using a differential scanning calorimeter equipped with a camera under heating conditions in which the temperature is raised from room temperature to the maximum foaming temperature of the foaming agent in 5 minutes and the temperature is maintained at the maximum foaming temperature of the foaming agent, the slope of a tangent drawn at the apex of the peak in the curve on the long-term side of the peak is set as C, and in a DSC curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under the above heating conditions, the slope of a tangent drawn at the apex of the peak in the curve on the long-term side of the exothermic peak is set as D, and in this case, C<D.

[0191] Here, differential scanning calorimetry (DSC) of the foaming agent was performed using the following method. First, 0.16 mg to 0.17 mg of the foaming agent was weighed in a container. Then, using a differential scanning calorimeter equipped with a camera, the temperature was increased and maintained at a nitrogen flow rate of 20 ml / min and at a heating condition of increasing the temperature from room temperature to the maximum foaming temperature of the foaming agent in 5 minutes and maintaining the maximum foaming temperature of the foaming agent.

[0192] In the expansion ratio-time curve of the blowing agent, the method for determining the tangent line drawn at the peak apex in the curve on the long time side of the peak is the same as the method described in the above "A. Method for producing article".

[0193] In addition, differential scanning calorimetry (DSC) of the adhesive composition was performed using the following method. First, 5.00 mg to 5.03 mg of the adhesive composition was weighed in a container. Then, using a differential scanning calorimeter, the temperature was increased and maintained at a nitrogen flow rate of 20 ml / min and at a heating condition of increasing the temperature from room temperature to the maximum foaming temperature of the foaming agent in 5 minutes and maintaining the temperature at the maximum foaming temperature of the foaming agent.

[0194] In the DSC curve of the adhesive composition, the method for determining the tangent line drawn at the apex of the exothermic peak in the curve on the long-time side of the exothermic peak is the same as the method described in the above "A. Method for producing article".

[0195] The method of superimposing the expansion ratio-time curve of the blowing agent and the DSC curve of the adhesive composition to form a single graph is the same as the method described in the above-mentioned "A. Method for producing article".

[0196] In addition, when the adhesive composition contains multiple foaming agents, at least one foaming agent only needs to satisfy C < D. Among the multiple foaming agents contained in the adhesive composition, it is preferred that the foaming agent with a higher content satisfies C < D. It is particularly preferred that all the multiple foaming agents contained in the adhesive composition satisfy C < D.

[0197] In the expansion rate-time curve of the foaming agent, when there are multiple peaks, at least one peak satisfies C<D. In the expansion rate-time curve, when there are multiple peaks, the adhesive composition usually contains multiple foaming agents. Among them, it is preferred that all peaks satisfy C<D.

[0198] In addition, in the DSC curve of the adhesive composition, when there are multiple exothermic peaks due to the curing reaction of the thermosetting resin, at least one exothermic peak satisfies C<D. In the DSC curve, when there are multiple exothermic peaks due to the curing reaction of the thermosetting resin, for example, the adhesive composition contains multiple thermosetting resins. Among them, it is preferred that the exothermic peak with a small slope B among the multiple exothermic peaks due to the curing reaction of the thermosetting resin satisfies C<D. It is particularly preferred that all the exothermic peaks satisfy C<D.

[0199] In the adhesive composition, C<D. The relationship between C and D is the same as the relationship between A and B described in the above-mentioned "A. Method for producing article".

[0200] The method for controlling the slope C is the same as the method for controlling the slope A described in the above-mentioned "A. Method for producing article".

[0201] The method for controlling the slope D is the same as the method for controlling the slope B described in the above-mentioned "A. Method for producing article".

[0202] In the expansion ratio-time curve of the foaming agent, the time from the peak top (the point where the expansion ratio of the foaming agent shows 100%) to the time when the shrinkage of the foaming agent stabilizes is the same as that described in the above-mentioned "A. Method for producing article".

[0203] In the DSC curve of the adhesive composition, the time from the top of the exothermic peak to the base line is the same as that described in the above-mentioned "A. Method for producing article".

[0204] The composition and preparation method of the adhesive composition are the same as those described in the above-mentioned "A. Method for producing article".

[0205] C. Foam adhesive sheet

[0206] The foamable adhesive sheet of the present disclosure is a foamable adhesive sheet having an adhesive layer, and the adhesive layer contains the above-mentioned adhesive composition.

[0207] The adhesive composition has been described in the above-mentioned section "B. Adhesive composition", and thus the description here is omitted.

[0208] In addition, since the foamable adhesive sheet has been described in the above-mentioned "A. Method for producing article 4. Foamable adhesive sheet", the description here is omitted.

[0209] The foamable adhesive sheet of the present disclosure may include a separator.

[0210] The spacer is not particularly limited as long as it can be peeled from the adhesive layer, and can have a strength that can protect the adhesive layer. As such a spacer, for example, a release film, a release paper, etc. can be cited. In addition, the spacer can have a single-layer structure or a multi-layer structure.

[0211] Examples of the single-layer separator include fluororesin films and the like.

[0212] In addition, as a spacer of a multilayer structure, for example, a laminate having a release layer on one or both sides of a substrate layer can be cited. As the substrate layer, for example, resin films such as polypropylene, polyethylene, polyethylene terephthalate, offset paper, coated paper, impregnated paper and the like can be cited. As the material of the release layer, as long as it is a material with release properties, there is no particular limitation, for example, silicone compounds, organic compound modified silicone compounds, fluorine compounds, aminoalkyd compounds, melamine compounds, acrylic compounds, polyester compounds, long-chain alkyl compounds, etc. can be cited. These compounds can use any of emulsion type, solvent type or solvent-free type.

[0213] The use of the foamable adhesive sheet of the present disclosure is not particularly limited. Among them, the foamable adhesive sheet of the present disclosure can be suitably used in the above-mentioned method for producing an article.

[0214] It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any technical solution having substantially the same structure and having the same effect as the technical concept described in the scope of the technical solution claimed for protection of the present disclosure is included in the technical scope of the present disclosure.

[0215] Example

[0216] [Production Examples 1 to 3]

[0217] First, adhesive compositions 1 to 3 having the compositions shown in the following Table 1 were prepared. In addition, the details of each material described in Table 1 are shown below. In addition, the unit in Table 1 is "parts by mass".

[0218] Acrylic resin: PMMA-PBuA-PMMA (partially acrylamide), Tg: -20°C, 120°C, Mw: 150,000

[0219] · Epoxy resin A: Bisphenol A novolac type, solid at room temperature, softening temperature: 70°C, epoxy equivalent: 210 g / eq, Mw: 1300, melt viscosity at 150°C: 0.5 Pa·s

[0220] ·Epoxy resin B: BPA phenoxy type, solid at room temperature, softening temperature: 110°C, epoxy equivalent: 8000g / eq, Mw: 50000

[0221] Curing agent A: α-(hydroxy (or dihydroxy) phenylmethyl)-ω-hydrogen poly[biphenyl-4,4'-diylmethylene (hydroxy (or dihydroxy) phenylene methylene)]

[0222] Curing catalyst: 2-phenyl-4,5-dihydroxymethylimidazole, average particle size: 3 μm, melting point: 230°C, reaction start temperature 145°C to 155°C, active region 155°C to 173°C (manufactured by Shikoku Chemical Industry Co., Ltd., 2PHZ-PW)

[0223] · Foaming agent: thermally expandable microcapsules, average particle size 10μm to 16μm, expansion start temperature 123℃ to 133℃, maximum expansion temperature 168℃ to 178℃, core: hydrocarbon, shell: thermoplastic polymer

[0224] Solvent: Methyl Ethyl Ketone

[0225]

[0226] A release film (PET spacer, manufactured by NIPPA, PET50×1-J2, thickness 50 μm) was used. The adhesive composition was applied to the release-treated surface of the release film using a sizer so that the thickness after application was 45 μm. Thereafter, the film was dried in an oven at 100° C. for 3 minutes to form an adhesive layer, thereby obtaining a foamable adhesive sheet.

[0227] [Evaluation 1]

[0228] (1) Differential scanning calorimetry of foaming agent

[0229] The foaming agent was measured by differential scanning calorimetry using a camera-equipped differential scanning calorimeter ("High Sensitivity Differential Scanning Calorimeter DSC7000X" manufactured by Hitachi High Tech Science Co., Ltd.) under heating conditions of 5 minutes of heating time from room temperature to 180°C and 15 minutes of holding time at 180°C.

[0230] (2) Differential Scanning Calorimetry of Adhesive Composition

[0231] The adhesive layer containing the adhesive composition was subjected to differential scanning calorimetry using a differential scanning calorimeter (“High Sensitivity Differential Scanning Calorimeter DSC7000X” manufactured by Hitachi High Tech Science) under heating conditions of 5 minutes of heating time from room temperature to 180° C. and 15 minutes of holding time at 180° C.

[0232] (3) Relationship between slope A and slope B

[0233] The method described in the above "A. Method for producing articles" was used to superimpose the expansion rate-time curve of the foaming agent and the DSC curve of each adhesive composition 1 to 3 to prepare a graph. The graph is shown in Fig. 9 (a) to (c). In addition, the slope A of the tangent line drawn at the top of the peak in the curve on the long time side of the peak in the expansion rate-time curve of the foaming agent is determined by the method described in the above "A. Method for producing an article". In addition, the slope B of the tangent line drawn at the top of the exothermic peak in the curve on the long time side of the exothermic peak in the DSC curve of the adhesive layer containing the adhesive composition is determined by the method described in the above "A. Method for producing an article".

[0234] (4) Bonding strength

[0235] Prepare 2 cold-rolled steel sheets SPCC-SD (length 100mm×width 25mm×thickness 1.6mm). Set a spacer (polyimide tape) at 15mm intervals on one steel plate. The thickness of the spacer is set to 140μm (the thickness of 2 overlapping polyimide tapes P-221 manufactured by Nitto Denko Corporation). Between the spacers, a foaming adhesive sheet cut into 12.5mm×25mm and peeled off the release film is configured, and another steel plate is configured from above it and fixed with a clip to obtain a test piece. The test piece is heated from room temperature to 180°C in 5 minutes using an IR heater (handheld heating furnace manufactured by ADVANCE RIKEN Co., Ltd.), and heated at 180°C for 30 minutes, thereby curing the foaming adhesive sheet. The shear strength (adhesive strength) of the heated test piece is measured using TENSILON RTF1350 (manufactured by A&D Co., Ltd.) in accordance with JIS K6850. The tensile speed is set to 10mm / min and the temperature is set to 23°C.

[0236]

[0237] [Production Example 4]

[0238] First, an adhesive composition 4 having the following composition was prepared.

[0239] <Composition of Adhesive Composition 4>

[0240] Acrylic resin (PMMA-PBuA-PMMA (partially acrylamide), Tg: -20°C, 120°C, Mw: 150,000): 40 parts by mass

[0241] Epoxy resin C (bisphenol A type, liquid at room temperature, epoxy equivalent: 184-194 g / eq): 45 parts by mass

[0242] Epoxy resin D (diaminodiphenylmethane type, high viscosity liquid, epoxy equivalent: 110-130 g / eq): 65 parts by mass

[0243] Epoxy resin E (silicone modified, epoxy equivalent: 1200 g / mol): 20 parts by mass

[0244] Silane coupling agent (3-glycidoxypropyltrimethoxysilane): 2 parts by mass

[0245] Curing agent B (phenol-formaldehyde polycondensate softening point 80°C, hydroxyl equivalent 104 g / mol): 6 parts by mass

[0246] Curing catalyst (2-phenyl-4,5-dihydroxymethylimidazole, average particle size: 3 μm, melting point: 230°C, reaction start temperature 145°C to 155°C, active region 155°C to 173°C (manufactured by Shikoku Chemical Industry Co., Ltd., 2PHZ-PW)): 10 parts by mass

[0247] · Foaming agent: thermally expandable microcapsules, average particle size 10 μm to 16 μm, expansion start temperature 123°C to 133°C, maximum expansion temperature 168°C to 178°C, core: hydrocarbon, shell: thermoplastic polymer: 20 parts by mass

[0248] Solvent (methyl ethyl ketone): 114 parts by mass

[0249] Polyethylene naphthalate (PEN film, manufactured by TOYOBO FILM SOLUTION, Teonex Q51, thickness 25 μm) was used as a substrate. The adhesive composition 1 used in the above-mentioned manufacturing example 1 was applied to one surface of the above-mentioned substrate using a sizer so that the thickness after application was 45 μm. Thereafter, it was dried in an oven at 100° C. for 3 minutes to form a first adhesive layer.

[0250] Then, a release film (PET spacer, manufactured by NIPPA, PET50×1-J2, thickness 50 μm) was used as a second spacer, and the adhesive composition 4 was applied to the release treated surface of the release film using a sizer so that the thickness after application was 45 μm. Thereafter, the film was dried in an oven at 100° C. for 3 minutes to form a second adhesive layer.

[0251] Then, the second adhesive layer side surface of the laminate having the substrate and the first adhesive layer is laminated with the second spacer and the second adhesive layer on the substrate side surface of the laminate having the substrate and the first adhesive layer, thereby obtaining a foamable adhesive sheet having the first adhesive layer, substrate, second adhesive layer and second spacer arranged in sequence.

[0252] [Evaluation 2]

[0253] (1) Differential scanning calorimetry of foaming agent

[0254] The blowing agent was measured by differential scanning calorimetry using a camera-equipped differential scanning calorimeter ("High Sensitivity Differential Scanning Calorimeter DSC7000X" manufactured by Hitachi High Tech Science Corporation) under heating conditions of a heating time from room temperature to 180°C of 1 minute to 65 minutes and a holding time at 180°C of 30 minutes.

[0255] (2) Differential Scanning Calorimetry of the Adhesive Composition from Which the Blowing Agent Was Removed

[0256] Regarding Adhesive Compositions 1 and 4, the composition obtained by removing the foaming agent from each adhesive composition was subjected to differential scanning calorimetry using a differential scanning calorimeter (“High Sensitivity Differential Scanning Calorimeter DSC7000X” manufactured by Hitachi High Tech Science Co., Ltd.) under heating conditions in which the heating time from room temperature to 180° C. was 1 minute to 65 minutes and the holding time at 180° C. was 30 minutes.

[0257] (3) Relationship between time T1 and time T2

[0258] For each heating condition, the expansion rate-time curve for the blowing agent and the DSC curve for the composition from which the blowing agent was removed were superimposed to form a graph. For Adhesive Composition 1, the graphs for the heating times of 5 minutes and 65 minutes are shown in FIG. Fig.10 (a) and (b). In addition, for Adhesive Composition 4, the graphs when the heating time is 5 minutes and 65 minutes are shown in Fig.10(a) and (b). In addition, in the expansion rate-time curve of the blowing agent, the time T1 of the peak apex is determined. In addition, in the DSC curve of the composition from which the blowing agent is removed, the time T2 of the exothermic peak apex is determined.

[0259] (4) Bonding strength

[0260] Prepare 2 cold-rolled steel plates SPCC-SD (length 100mm×width 25mm×thickness 1.6mm). Set spacers (polyimide tape or fluoro tape) at intervals of 15mm on one steel plate. The thickness of the spacer is set to about 370μm (the thickness of overlapping 2 pieces of polyimide tape P-221 manufactured by Nitto Denko Corporation and 1 piece of fluororesin adhesive tape 8410 manufactured by Teraoka Manufacturing Co., Ltd.). A foaming adhesive sheet cut into 12.5mm×25mm and peeled off the second spacer is arranged between the spacers, and another steel plate is arranged from above it and fixed with a clip to obtain a test piece. The test piece is heated from room temperature to 180°C in more than 1 minute and less than 65 minutes using an IR heater (handheld heating furnace manufactured by ADVANCE Technology Co., Ltd.), and heated at 180°C for 30 minutes to cure the foaming adhesive sheet. The shear strength (adhesive strength) of the heated test piece was measured using TENSILON RTF1350 (manufactured by A&D Co., Ltd.) in accordance with JIS K6850. The tensile speed was 10 mm / min and the temperature was 23°C.

[0261]

[0262] From Tables 2 and 3, it was confirmed that when A<B and the adhesive composition was heated so as to satisfy T1<T2 in the bonding step, the bonding strength was improved.

[0263] [Evaluation 3]

[0264] (1) Maximum foaming temperature of foaming agent

[0265] The foaming agent was measured by differential scanning calorimetry at a heating rate of 31°C / min using a differential scanning calorimeter equipped with a camera ("High Sensitivity Differential Scanning Calorimeter DSC7000X" manufactured by Hitachi High Tech Science). In the foaming rate-time curve of the foaming agent, the temperature at the top of the peak was defined as the maximum foaming temperature. The maximum foaming temperature was 174.5°C.

[0266] (2) Differential scanning calorimetry of foaming agent

[0267] The foaming agent was subjected to differential scanning calorimetry using a camera-equipped differential scanning calorimeter (“High Sensitivity Differential Scanning Calorimeter DSC7000X” manufactured by Hitachi High Tech Science Co., Ltd.) under heating conditions of a heating time of 5 minutes from room temperature to the maximum foaming temperature (174.5° C.) and a holding time of 15 minutes at the maximum foaming temperature (174.5° C.).

[0268] (3) Differential Scanning Calorimetry of Adhesive Composition

[0269] The adhesive layers containing the adhesive compositions 1 to 3 used in Production Examples 1 to 3 were subjected to differential scanning calorimetry using a differential scanning calorimeter (“High Sensitivity Differential Scanning Calorimeter DSC7000X” manufactured by Hitachi High Tech Science Co., Ltd.) under heating conditions of a heating time of 5 minutes from room temperature to the maximum foaming temperature (174.5° C.) and a holding time of 15 minutes at the maximum foaming temperature (174.5° C.).

[0270] (4) Relationship between slope C and slope D

[0271] The expansion rate-time curve of the foaming agent and the DSC curve of each adhesive composition are superimposed by the method described in the above "A. Method for producing articles" to prepare a graph. In addition, the slope C of the tangent drawn at the top of the peak in the curve on the long-time side of the peak in the expansion rate-time curve of the foaming agent is obtained by the method described in the above "A. Method for producing articles". In addition, the slope D of the tangent drawn at the top of the exothermic peak in the curve on the long-time side of the exothermic peak in the DSC curve of the adhesive layer containing the adhesive composition is obtained by the method described in the above "A. Method for producing articles".

[0272] (5) Bonding strength

[0273] The adhesive strength was measured by the same method as that described in the above Evaluation 1.

[0274] In the case of C<D, it was confirmed that the adhesive strength was improved.

[0275] [Evaluation 4]

[0276] (1) Bonding strength

[0277] The adhesive strength of the foamable adhesive sheet of Manufacturing Example 4 was measured by the same method as described in the above Evaluation 2. At this time, the foamable adhesive sheet was heated under the heating conditions of 15 minutes for the heating time from room temperature to the heating temperature, 150°C or higher and 200°C or lower, and 0 minutes or higher and 120 minutes or lower for the holding time at the heating temperature. The results are shown in Fig.12 middle.

[0278] In addition, after the bond strength is measured, the cohesive failure rate is calculated. The cohesive failure rate is the ratio of the area of ​​the cohesive failure portion to the entire bond area. The results are shown in Fig.13 middle.

[0279] Fig.12 and Fig.13 This suggests that there is a preferred range in the heating temperature.

[0280] Description of Reference Numerals

[0281] 1 Adhesive layer, 1a First adhesive layer, 1b Second adhesive layer, 2 Base material, 10 Foamable adhesive sheet, 11 Adhesive sheet after foaming and curing, 20a First component, 20b Second component, 100 Article.

Claims

1. A method for manufacturing an article, the method comprising: A disposing step of disposing an adhesive composition containing a thermosetting resin and a foaming agent between the first member and the second member; as well as a bonding step of heating the adhesive composition to foam and solidify the adhesive composition to bond the first member to the second member; The foaming agent is a heat-expandable microcapsule, In a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry under the heating conditions in the bonding step using a differential scanning calorimeter equipped with a camera, the slope of a tangent line drawn at the peak apex in the curve on the long time side of the peak is defined as A, In a DSC curve with time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under the heating conditions in the bonding step, the slope of a tangent drawn at the top of the exothermic peak in the curve on the long time side of the exothermic peak is defined as B. In this case, A<B, In a foaming rate-time curve in which time is the horizontal axis and the foaming rate of the foaming agent is the vertical axis when the foaming agent is subjected to differential scanning calorimetry using a differential scanning calorimeter equipped with a camera, the time of the peak top is defined as T1. In a DSC curve having time as the horizontal axis and heat flow as the vertical axis when differential scanning calorimetry is performed on a composition obtained by removing the foaming agent from the adhesive composition, the time of the top of the exothermic peak is set to T2. At this time, in the bonding step, the adhesive composition is heated in a manner such that T1<T2.

2. The method for manufacturing an article according to claim 1, wherein: The heating temperature in the bonding step is within a range of ±20° C. of the maximum foaming temperature of the foaming agent.

3. The method for manufacturing an article according to claim 1 or 2, wherein: In the arrangement step, a foamable adhesive sheet having an adhesive layer containing the adhesive composition is used to arrange the foamable adhesive sheet between the first member and the second member.

4. An adhesive composition comprising a thermosetting resin and a foaming agent, The foaming agent is a heat-expandable microcapsule, In a foaming rate-time curve with time as the horizontal axis and the foaming rate of the foaming agent as the vertical axis when the foaming agent is subjected to differential scanning calorimetry measurement using a differential scanning calorimeter equipped with a camera under heating conditions in which the temperature is raised from room temperature to the maximum foaming temperature of the foaming agent over 5 minutes and the temperature is maintained at the maximum foaming temperature of the foaming agent, the slope of a tangent line drawn at the peak apex in the curve on the long time side of the peak is defined as C, In a DSC curve having time as the horizontal axis and heat flow as the vertical axis when the adhesive composition is subjected to differential scanning calorimetry under the heating conditions, the slope of a tangent drawn at the top of the exothermic peak in the curve on the long time side of the exothermic peak is defined as D. In this case, C<D, In a foaming rate-time curve in which time is the horizontal axis and the foaming rate of the foaming agent is the vertical axis when the foaming agent is subjected to differential scanning calorimetry using a differential scanning calorimeter equipped with a camera, the time of the peak top is defined as T1. In a DSC curve with time as the horizontal axis and heat flow as the vertical axis when differential scanning calorimetry is performed on the composition obtained by removing the foaming agent from the adhesive composition, the time of the top of the exothermic peak is defined as T2. At this time, the composition is heated before use so that T1<T2. 5 . A foamable adhesive sheet comprising an adhesive layer, wherein the adhesive layer contains the adhesive composition according to claim 4 .

Citation Information

Patent Citations

  • Coating method

    JP1987023477A

  • Tacky adhesive layer and tacky adhesive sheet

    JP2014065889A

  • Adhesive sheet

    JP2019203062A